THE EFFECT OF PUBLIC EXPENDITURES COMPONENTS ON ECONOMIC GROWTH IN TURKEY (Third Sector Social Economic Review, 2021)
In this study, the effect of public expenditure components on economic growth was analyzed to discuss the relationship between public expenditure and economic growth specific to Turkey’s economy. In the first model of the empirical analysis, where three different models are discussed, the economic classification of public expenditures is considered, while the functional classification is considered in the second model. The last model was created with expenditure components that stand out for the development of the country and whose effects are frequently emphasized in the literature.Due to the limitation of access to data, the ARDL model for the period 1975-2017 was estimated in the first 2 models, while VAR and Impulse-Response Analysis were performed within the scope of the 1984-2017 period in the last model. According to the findings, foreign debt payments, current expenditures, health expenditures, and defense expenditures have a decreasing effect on economic growth in the long term, while education expenditures, housing expenditures, and investment expenditures have a positive effect. In addition, according to Toda Yamamoto causality analysis in both models, there is a causal relationship from economic growth to education, housing and defense expenditures. According to the results of VAR and Impulse-Response Analysis, the most influential variables on the changes in GDP are the number of patents, transportation expenditures, public manufacturing industry expenditures, defense expenditures, and agricultural expenditures, respectively.
Keywords: Public Expenditures Components; Economic Growth; ARDL Boundary Test Approach; VAR Analysis; Impulse-Response Analysis.